"Learning Implementation of the Akhlak Lil Banin Book in Akhlak Building of Santri at Qotrun Nada Islamic Boarding School Depok City" - Muhammad Syafiq Ashfa Hubbi (Journal of Social Research, 2022)
Background: The learning process of the Lil Banin Akhlak book at the Qotrun Nada Islamic Boarding School in Depok City, namely by using various learning methods, namely by the method: Sorogan, this method uses book learning by facing the ustadz one by one by bringing the book he will study. Halaqah, this method uses a good teaching system and is trained with the ustadz system of reading the text of the book while the students listen and listen to the explanation directly from the ustadz who is teaching. Bandongan, the bandongan method is the most important in the Qotrun Nada Islamic Boarding School environment, a teaching method by the way the teacher reads, translates, and explains. Objective: This study aims to analyze the learning of the Lil banin moral book in the formation of santri morals in the qotrun nada islamic boarding school in Depok city. Methods: This study uses ethnomethodological and psychological-paedagogic research methods. Ethnomethodological methods often referred to as phenomenological methods include qualitative, naturalistic methods that study how social behavior can be described as it is (naturally), and seek to understand how people perceive, explain and describe their living systems Result: The result of the implementation of the learning of the Lil Banin Akhlak book in the formation of santri morals at the Qotrun Nada Islamic Boarding School in Depok City, is After the students follow the learning the Lil Banin Akhlak book, the results of change in their behavior can be seen, both from good and bad changes. Conclusion: In the results of this study, it can be seen that all male students kissed the hand of the teacher or ustadznya when they had finished studying the book they had studied. Some students put their teachers or ustadz first to leave the classroom before their turn. And among the other students, some bowed their heads and smiled when their ustadz passed in their midst and their greetings and language began to improve, both in communicating with aside wal asatidzah and fellow peers both smaller than him and older than him. Keywords: implementation, learning, morals, akhlak Lil banin